Gamification with natural language processing: A pathway to improved English speaking for EFL students - Shella Gherina Saptiany; C Susmono Widagdo; Abel Julia Istifary; Aruf Mustofa (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
Advances in artificial intelligence and gamification have transformed language learning by offering interactive, feedback-rich, and engaging environments that go beyond traditional instruction. In this context, this study investigates the impact of Natural Language Processing (NLP)-based gamification applications on the English speaking performance of students learning English as a Foreign Language (EFL). Using a quasi-experimental design, 90 tourism students were divided into three groups: two experimental groups using ELSA Speak and Duolingo, and a control group following conventional learning methods. Speaking tests were administered before and after a ten-session intervention, and the results were analyzed using Quantitative. The findings revealed substantial improvements in the speaking skills of students using NLP-based gamification applications. Both ELSA and Duolingo produced significant gains in pronunciation, fluency, and overall speaking performance compared to the control group, with Duolingo demonstrating slightly more consistent improvements. Large effect sizes confirmed the practical significance of these results, while the negligible changes in the control group underscored the effectiveness of technology-based interventions.